Peran Ovicidal Herbal Serbuk Biji Pepaya (Carica papaya L) Matang Terhadap Telur Cacing Ascaris suum - Ardana, Ida (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
An in vitro experiment to determine the effect of ground mature papaya seeds on characteristics of Ascaris suum eggs was conducted employing a Randomized Block Design. Four doses of the ground preparation – 0 mg (as control), 285 mg, 570 mg, and 855 mg- in 40 ml of physiological saline solution – were used to soak 100 eggs. Six replications were made. Worm eggs were obtained from the uteruses of ascariasis pigs slaughtered at the local abattoir. The eggs characteristics observed after application of the treatment were the embryo formation ability and the damage of egg cell layers. Statistical analysis was applied to the data collected using Analysis of Variance followed by Least Significance Test. The results showed that the ability of treated eggs to form embryos was significantly lower than that of control. Such a decrease in embryo formation ability could be related to the formation of granule (albumen coagulation) in the egg cell layers after the treatments. All treated eggs possessed such granules.